PENGARUH REWARD DAN PUNISHMENT TERHADAP DISIPLIN BELAJAR PESERTA DIDIK: (Survey Pada Peserta Didik Kelas XII IPS dan XII IPA SMA Negeri 1 Karangnunggal Tahun Ajaran 2023/2024) - Sintya Marwati; Ai Nur Solihat; Kurniawan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The research aims to determine the effect of rewards and punishment on students' learning discipline. The research method uses quantitative with an explanatory survey design. The population of Class XII IPS and XII IPA students at SMA Negeri 1 Karangnunggal for the 2023/2024 academic year is 251 people. The sampling technique used was saturated sampling, so the total sample taken was 251 people. Data collection techniques in this research used questionnaires, statistical tests used multiple linear regression and coefficient of determination, and the hypothesis tests used were partial tests (t tests) and simultaneous tests (f tests). The results of the research show that reward and punishment have an effect on students' learning discipline partially or simultaneously.